Relative importance of shoot and root competition in dry-seeded rice growing with junglerice (Echinochloa colona) and ludwigia (Ludwigia hyssopifolia) - Chauhan, Bhagirath S.; Johnson, David E. (Cambridge University Press, 2010)
Two separate studies were conducted to determine the relative importance of root and shoot competition in dry direct-seeded rice growing with junglerice and ludwigia. By growing rice in pots placed within larger pots such that the roots of the plants were either separated from or free to mingle with those of neighboring weeds, or by growing rice in the same pots but in the absence of weeds, the relative importance of shoot and root competition can be described. When rice was grown together with either weed species, shoot competition reduced the growth and yield of rice more than root competition. Results suggest that shoot competition for light may be the primary mechanism determining competitive outcomes between dry direct-seeded rice and junglerice or ludwigia. Junglerice was more competitive than ludwigia, which may reflect the C4 metabolism efficiency of junglerice compared to the C3 metabolism of ludwigia. Rice grain yield was highly correlated with above- and belowground biomass. The results also suggest the importance of measuring the whole plant when seeking to understand differences in the competitive ability of dry direct-seeded rice.